Management of foreign body ingestion in adults: Time to STOP and rethink endoscopy - Tambakis, George; Schildkraut, Tamar; Delaney, Isabella; Gilmore, Robert; Loebenstein, Moshe; Taylor, Andrew; Holt, Bronte; Tsoi, Edward H; Cameron, Georgina; Demediuk, Barbara; Miller, Ashley; Connell, William; Wright, Emily; Thompson, Alexander; Holmes, Jacinta (Endoscopy International Open, 2023)
Background and study aims Foreign body ingestion is a common cause for Emergency Department presentation. In adults, foreign body ingestion is more common in patients with underlying psychiatric comorbidity, the elderly, alcohol intoxication, and in prisoners. This study reviewed the management of patients presenting to a tertiary hospital with foreign body ingestion.Patients and methods A retrospective review of patients presenting with foreign body ingestion to a tertiary hospital in Melbourne, Victoria, was undertaken from January 2017 to December 2021. Data collected included patient demographics, type of foreign body, length of stay, imaging modalities, management strategies, and complications. High-risk ingestion was defined as sharp objects, length >5 cm, diameter >2.5 cm, button battery and/or magnet ingestion or esophageal as per international guidelines.Results A total of 157 presentations by 63 patients with foreign body ingestion occurred between 2017 and 2021 (50% male; median age 30 years). Of the patients, 56% had underlying psychiatric comorbidities. The majority of presentations occurred in prisoners (65%). The most commonly ingested objects were batteries (23%), alleged drug-containing balloons (17%), razor blades (16%), and miscellaneous (40%). High-risk ingestion occurred in approximately two-thirds of presentations. Conservative management was the most common approach in 55% of patients. Complications, defined as perforation, bowel obstruction or fistula formation, did not occur in this cohort despite more than half presenting with high-risk ingestions. Thirty-day re-presentation rates were high (31%) and that was most common in patients with intentional ingestion, underlying mental health disorders, and a documented history of self-harm.Conclusions Conservative management for patients presenting with recurrent high-risk foreign body ingestion was safe in appropriately selected cases. Re-presentation is common and poses significant challenges for health care providers.
Keywords: Foreign bodies; GI surgery